A Framework for an IP-based DVB Transmission Network. (6th May 2010) - Ewald-Arostegui, Nimbe L.; Fairhurst, Gorry; Yun-Garcia, Ana
Abstract : One of the most important challenges for next generation all-IP networks is the convergence and interaction of wireless and wired networks in a smooth and efficient manner. This challenge will need to be faced if broadcast transmission networks are to converge with IP infrastructure. The 2nd generation of DVB standards supports the Generic Stream, allowing the direct transmission of IP-based content using the Generic Stream Encapsulation (GSE), in addition to the native Transport Stream (TS). However, the current signalling framework is based on MPEG-2 Tables that rely upon the TS. This paper examines the feasibility of providing a GSE signalling framework, eliminating the need for the TS. The requirements and potential benefits of this new approach are described. It reviews prospective methods that may be suitable for network discovery and selection and analyses different options for the transport and syntax of this signalling metadata. It is anticipated that the design of a GSE-only signalling system will enable DVB networks to function as a part of the Internet.